A growing problem of methanol poisonings: A retrospective analysis of 47 patients in a single-center in Turkey (Annals of Medical Research, 2021)
Aim: The present study was aimed to determine the epidemiological features, clinical signs, and risk factors of methanol poisonings in our region. As all countries, methanol poisoning continues to be a serious problem in Turkey. The epidemiology of methanol poisoning varies between countries, even between regions of the same country. It is important to evaluate the regional factors to decrease morbidity and mortality.Materials and Methods: This descriptive retrospective study was conducted in a regional tertiary hospital. The medical records of all methanol poisoning-related admissions to the emergency department between January 2016 and December 2020 were retrospectively reviewed. Etiology of poisoning, demographic characteristics, laboratory results including methanol levels, administered treatments, and mortality were recorded.Results: 47 patients aged 18-67 years (mean 31.55±14,88 years) were included in the study. Thirty-nine (82.9%) of the patients were male and 8 (17.1%) of them were female. The vast majority of patients (n = 33, 70.3%) had nausea and vomiting. Twenty (42.5%) patients had blurred vision and 1 (2.1%) patient had blindness. Three (6.3%) patients were in a stupor and 4 (8.5%) were in a coma. The mortality rate of methanol poisonings was 12.7% (n=6). 28 (59.5%) patients survived without complications, whereas, 13 (27.6%) patients survived with a neurological sequel.Conclusions: Methanol poisoning is a serious problem among developing countries, where alcohol is not legal and cheap. High serum methanol levels are associated with a poor prognosis. Time spent from ingestion to treatment is critical to avoid complications and mortality, therefore clinicians should keep in mind methanol poisoning during differential diagnosis in such patients.
Keywords: Blurred vision; emergency medicine; home-made alcohol; illegality; methanol level; mortality; poisoning